Plant stanol esters might optimise the immune response and improve the SARS-CoV-2/COVID-19 vaccine efficacy in overweight and obese subjects - Plat, Jogchum; van Brakel, Lieve; Mensink, Ronald P. (British journal of nutrition, 2022)
Antibody titters in overweight or obese subjects (BMI > 25 kg/m2) from the control group were at least half of those in normal-weight subjects (BMI < 25 kg/m2), showing that a high BMI indeed compromised the immune response. [...]upon plant stanol ester consumption, antibody titters increased by 18 % in normal-weight asthma patients and by 73 % in asthma patients with overweight and obesity. Based on these findings, we now hypothesise that people with a higher BMI might particularly benefit from plant stanol consumption several weeks prior and after receiving the COVID-19 vaccination. [...]we recently initiated another double-blind placebo-controlled intervention trial to evaluate the effects of a daily intake of 4 g plant stanols as their fatty acid esters in subjects with overweight or obesity (BMI 27–35 kg/m2). Recruitment and execution have started. Besides possible effects on T cell behaviour, another mechanism related to plant stanol ester consumption may be worthwhile to explore in the context of COVID-19 exposure.